The Philips College, Nikosia (Zypern) - Platritis, Christos (Revista de Filología Alemana, 2011)
Since the collapse of Christianity in the Ancient World and its spread in Europe, a major restraint and an inexhaustible conservatism can be observed, with only a few exceptions, in all areas of life, when it comes to sexuality as a social phenomenon. After a reference to cultural, mythological and historical evidence relating to the human perception of sexuality and on sexuality in the tension between individual and society, the second part of my article délas with the different views of known educators, philosophers and psychologists, who from the mid-18th to the beginning of the 20th Century to addressed sexual the issue of sexuality. The third part is the nucleus of the work and deals with the question of way in which literary texts capture sexuality as a social phenomenon, the social position of men and women, and their sexual relationship.